Optimization of GaN Nanowires Reformation Process by Metalorganic Chemical Vapor Deposition for Device‐Quality GaN Templates. Issue 4 (12th December 2019) - Delgado Carrascon, Rosalia; Tran, Dat Quoc; Sukkaew, Pitsiri; Mock, Alyssa; Ciechonski, Rafal; Ohlsson, Jonas; Zhu, Yadan; Hultin, Olof; Monemar, Bo; Paskov, Plamen P.; Samuelson, Lars; Darakchieva, Vanya
Abstract : Herein, the potential of reformed GaN nanowires (NWs) fabricated by metalorganic chemical vapor deposition (MOCVD) for device‐quality low‐defect density templates and low‐cost alternative to bulk GaN substrates is demonstrated. The effects of epilayer thickness and NW reformation conditions on the crystalline quality and thermal conductivity of the subsequent GaN epilayers are investigated. Smooth surfaces with atomically step‐like morphologies with no spirals are achieved for GaN epilayers on the reformed NW templates, indicating step‐flow growth mode. It is further found that annealing of the NWs at a temperature of 1030 °C in the presence of NH3 and H2, followed by a coalescence done at the same temperature under planar growth conditions, leads to the most efficient screw dislocation density reduction by nearly an order of magnitude. At these optimized conditions, the growth takes place in a layer‐by‐layer fashion, producing a smooth surface with a root mean square (RMS) roughness of 0.12 nm. The highest thermal conductivity of k = 206 W m −1  K −1, approaching the respective value of bulk GaN, is obtained for the optimized 2 μm‐thick GaN layer. The thermal conductivity results are further discussed in terms of the phonon‐dislocation and the phonon‐boundary scattering. Abstract : Herein, the potential of templates produced by reformation and coalescence of GaN nanowires via metalorganic vapor phase epitaxy as a promising alternative for cost‐effective GaN templates for electronic and optoelectronic devices is demonstrated.